Method for manufacturing sintered bodies, inserts, cutting tools, and machined parts

JP2026166314APending Publication Date: 2026-10-14KYOCERA CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025059179
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0008】 実施形態の一態様によれば、耐久性を向上させることが可能な焼結体を提供することが可能になる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166314000001_ABST
    Figure 2026166314000001_ABST
Patent Text Reader

Abstract

To provide a sintered body capable of improving durability at elevated temperatures. [Solution] The sintered body comprises a hard phase containing cubic boron nitride and a bonding phase containing AlN and Al2O3, which binds the hard phase. The intensity of the diffraction peak I_AlN(100) corresponding to the (100) plane of the AlN crystal lattice in the X-ray diffraction pattern and the intensity of the diffraction peak I_Al2O3(104) corresponding to the (104) plane of the Al2O3 crystal lattice in the X-ray diffraction pattern satisfy the relationship I_AlN(100)>I_Al2O3(104). The crystallite size S_AlN(100) of AlN with respect to the (100) plane of the AlN crystal lattice and the crystallite size S_Al2O3(104) of Al2O3 with respect to the (104) plane of the Al2O3 crystal lattice satisfy the relationship S_Al2O3(104)>S_AlN(100).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Embodiments of the present disclosure relate to a sintered body, an insert, a cutting tool, and a method for manufacturing a cut workpiece.

Background Art

[0002] Cubic boron nitride (cBN: cubic Boron Nitride) has the second highest hardness next to diamond and is excellent in chemical stability. For this reason, cBN-based sintered bodies are widely used as cutting tools for machining ferrous metals such as hardened steel, cast iron, or sintered alloys.

[0003] For example, a cBN-based sintered body is formed by bonding a plurality of cBN particles via a bonding phase, and the bonding phase contains Al compound particles containing at least one of AlN and Al₂O₃ (see, for example, Patent Document 1).

Prior Art Documents

Patent Documents

[0004]

Patent Document 1

Summary of the Invention

Problems to be Solved by the Invention

[0005] For example, in order to improve the efficiency of cutting work using a cutting tool, a cutting tool capable of performing favorable cutting work even when the cutting load increases is demanded. For example, a cutting tool having high durability even when the temperature rises during cutting work is demanded. As described above, the conventional technology still has room for further improvement in terms of enhancing durability.

[0006] One aspect of the embodiments has been made in view of the above, and an object thereof is to provide a sintered body capable of improving durability.

Means for Solving the Problems

[0007] A sintered body according to one embodiment comprises a hard phase containing cubic boron nitride and a bonding phase containing AlN and Al2O3 and bonding the hard phase, wherein the intensity of the diffraction peak I_AlN(100) corresponding to the (100) plane of the AlN crystal lattice in the X-ray diffraction pattern and the intensity of the diffraction peak I_Al2O3(104) corresponding to the (104) plane of the Al2O3 crystal lattice in the X-ray diffraction pattern satisfy the relationship I_AlN(100)>I_Al2O3(104), and the crystallite size S_AlN(100) of AlN with respect to the (100) plane of the AlN crystal lattice and the crystallite size S_Al2O3(104) of Al2O3 with respect to the (104) plane of the Al2O3 crystal lattice satisfy the relationship S_Al2O3(104)>S_AlN(100). [Effects of the Invention]

[0008] According to one embodiment, it becomes possible to provide a sintered body that can improve durability. [Brief explanation of the drawing]

[0009] [Figure 1] Figure 1 is a perspective view showing an example of an insert according to the embodiment. [Figure 2] Figure 2 is a side cross-sectional view showing an example of an insert according to the embodiment. [Figure 3] Figure 3 is a schematic diagram illustrating the cross-sectional structure of a sintered body according to an embodiment. [Figure 4] Figure 4 is a schematic diagram illustrating the cross-sectional structure of the binder phase contained in the sintered body according to the embodiment. [Figure 5] Figure 5 is a schematic diagram illustrating the X-ray diffraction pattern of a sintered body according to an embodiment. [Figure 6] Figure 6 is a front view showing an example of a cutting tool according to the embodiment. [Figure 7A] Figure 7A is a schematic diagram showing one step in the manufacturing method of a machined workpiece according to the embodiment. [Figure 7B]Figure 7B is a schematic diagram showing one step in the manufacturing method of a machined workpiece according to the embodiment. [Figure 7C] Figure 7C is a schematic diagram showing one step in the manufacturing method of a machined workpiece according to the embodiment. [Figure 8] Figure 8 shows the X-ray diffraction pattern of a cBN sintered body according to an example. [Figure 9] Figure 9 shows the X-ray diffraction pattern of a cBN sintered body according to a comparative example. [Figure 10] Figure 10 shows the results of wear resistance evaluation tests for cutting tools according to the examples and cutting tools according to the comparative examples. [Modes for carrying out the invention]

[0010] Hereinafter, with reference to the drawings, embodiments (hereinafter referred to as "Embodiments") for carrying out the manufacturing methods of sintered bodies, inserts, cutting tools, and machined works according to this disclosure will be described in detail. The manufacturing methods of sintered bodies, inserts, cutting tools, and machined works according to this disclosure are not limited to the embodiments described below. Each embodiment can be combined as appropriate without contradicting the content. In the following embodiments, the same parts are denoted by the same reference numerals, and redundant descriptions are omitted.

[0011] In the embodiments described below, expressions such as "constant," "orthogonal," "perpendicular," or "parallel" may be used, but these expressions do not require strict "constant," "orthogonal," "perpendicular," or "parallel." In other words, each of the above expressions allows for deviations such as manufacturing accuracy and / or installation accuracy.

[0012] <insert> First, an example of an insert according to the embodiment will be described with reference to Figures 1 and 2. Figure 1 is a perspective view showing an example of an insert according to the embodiment. As shown in Figure 1, the insert 1 according to the embodiment is an insert for a cutting tool and has a hexahedron shape in which the top and bottom surfaces (the surfaces intersecting the Z-axis shown in Figure 1) are parallelograms.

[0013] The insert 1 according to the embodiment includes a main body part 2 and a base body 10. The main body part 2 is an example of an insert main body. The base body 10 is attached to the main body part 2 via a joining material 40 (see FIG. 2) to be described later. In this manner, the base body 10 is positioned on the main body part 2.

[0014] The main body part 2 is formed of, for example, a cemented carbide. The cemented carbide contains W (tungsten), specifically WC (tungsten carbide). The cemented carbide may contain Ni (nickel) and / or Co (cobalt). The main body part 2 may be formed of cermet. The cermet contains, for example, Ti (titanium), specifically TiC (titanium carbide) or TiN (titanium nitride). Further, the cermet may contain Ni and / or Co.

[0015] A seating surface 4 for attaching the base body 10 is positioned at an end portion of the main body part 2. A through hole 5 penetrating the main body part 2 vertically is positioned at a central portion of the main body part 2. A screw 75 for attaching the insert 1 to a holder 70 to be described later is inserted into the through hole 5 (see FIG. 6).

[0016] The base body 10 is attached to the seating surface 4 of the main body part 2. Thereby, the base body 10 is integrated with the main body part 2.

[0017] The base body 10 has a first surface 6 (here, the upper surface) and a second surface 7 (here, the side surface) connected to the first surface 6. In the embodiment, the first surface 6 functions as a "rake face", and the second surface 7 functions as a "flank face". A cutting edge 8 is positioned on at least a part of the ridge line where the first surface 6 and the second surface 7 intersect, and the insert 1 cuts a workpiece by bringing the cutting edge 8 into contact with the workpiece.

[0018] The substrate 10 includes a sintered body. The substrate 10 includes a cubic boron nitride (cBN) sintered body (hereinafter referred to as "cBN sintered body"). The substrate 10 may be composed of a cBN sintered body. The cBN sintered body contains a plurality of cubic boron nitride (cBN) particles. In the cBN sintered body, the plurality of cBN particles are bonded together via a bonding phase. The specific composition of the cBN sintered body will be described later. The substrate 10 is not limited to a plurality of cBN particles, but may also contain particles such as hexagonal boron nitride (hBN), rhombohedral boron nitride (rBN), or wurtzite boron nitride (wBN).

[0019] Figure 2 is a side cross-sectional view showing an example of an insert according to the embodiment. As shown in Figure 2, a substrate 30 made of, for example, cemented carbide or cermet may be located on the lower surface of the base body 10. In this case, the base body 10 is joined to the seating surface 4 of the main body 2 via the substrate 30 and a bonding material 40. The bonding material 40 is, for example, brazing material. In parts of the main body 2 other than the seating surface 4, the base body 10 may be joined to the main body 2 via the bonding material 40.

[0020] In this embodiment, only the substrate 10, which is part of the insert 1, contains the cBN sintered body, but the entire insert 1 may contain the cBN sintered body.

[0021] The substrate 10 may be covered with a coating film 20. The coating film 20 covers the substrate 10 for purposes such as improving the wear resistance and heat resistance of the substrate 10. In the example in Figure 2, the coating film 20 covers the main body 2 and the substrate 10 completely. However, the coating film 20 does not need to be located on the substrate 10, but at least on top of it. The coating film 20 may be located on top of the main body 2. If the coating film 20 is located on the upper surface of the substrate 10, the wear resistance and heat resistance of the upper surface of the substrate 10 will be improved. If the coating film 20 is located on the side surface of the substrate 10, the wear resistance and heat resistance of the side surface of the substrate 10 will be improved.

[0022] The coating film 20 may include a metal layer and a hard layer. The metal layer is located between the substrate 10 and the hard layer. The metal layer has higher adhesion to the substrate 10 than the hard layer. Examples of metal elements having such properties include Zr (zirconium), V (vanadium), Cr (chromium), W, Al (aluminum), Si (silicon), and Y (yttrium). The metal layer contains at least one of the above metal elements.

[0023] The hard layer exhibits superior wear resistance compared to the metal layer. The hard layer may have one or more metal nitride layers. For example, the hard layer may include a plurality of first metal nitride layers and a plurality of second metal nitride layers, with the first metal nitride layers and second metal nitride layers being alternately stacked. The first metal nitride layers are located on top of the metal layer.

[0024] For example, the metal layer may contain Al and Cr. In this case, the first metal nitride layer may contain Al. Specifically, the first metal nitride layer may be an AlTiN layer containing AlTiN, which is a nitride of Al and Ti. The second metal nitride layer may be an AlCrN layer containing AlCrN, which is a nitride of Al and Cr.

[0025] In this way, by positioning the first metal nitride layer, which contains the metal present in the metal layer, on top of the metal layer, the adhesion between the metal layer and the hard layer is high. As a result, the hard layer is less likely to peel off from the metal layer, and therefore the durability of the coating film 20 is high.

[0026] The AlTiN layer as the first metal nitride layer is excellent in, for example, wear resistance, in addition to adhesion to the above-mentioned metal layer. The AlCrN layer as the second metal nitride layer is excellent in, for example, heat resistance and oxidation resistance. As described above, the coating film 20 includes the first metal nitride layer and the second metal nitride layer having mutually different compositions, whereby characteristics such as wear resistance and heat resistance of the hard layer can be controlled. Thereby, the tool life of the insert 1 can be extended. For example, in the hard layer according to the embodiment, mechanical properties such as adhesion to the metal layer and wear resistance can be improved while maintaining the excellent heat resistance possessed by AlCrN.

[0027] <Specific Configuration of cBN Sintered Body> Next, a specific configuration of the sintered body included in the base body 10 will be described with reference to FIG. 3 and FIG. 4. FIG. 3 is a schematic view illustrating a cross-sectional structure of the sintered body according to the embodiment. FIG. 4 is a schematic view illustrating a cross-sectional structure of a binder phase included in the sintered body according to the embodiment.

[0028] As shown in FIG. 3, the cBN sintered body 11 as the sintered body included in the base body 10 includes a hard phase 12 and a binder phase 13. The hard phase 12 contains cubic boron nitride (cBN). The hard phase 12 includes a plurality of cubic boron nitride particles (cBN particles) 12a. The hard phase 12 may contain cBN as the main component of the hard phase 12. Here, the main component of the hard phase 12 means 98% by mass or more relative to the mass of the hard phase 12. The binder phase 13 binds the hard phase 12. That is, the binder phase 13 binds at least the plurality of cBN particles 12a.

[0029] The hard phase 12 and the binder phase 13 included in the cBN sintered body 11 are confirmed, for example, by taking a photograph of a cross section of the base body 10. The photograph of the cross section of the base body 10 is obtained, for example, by using a scanning electron microscope (SEM). Examples of the scanning electron microscope include JSM-7100F (manufactured by JEOL).

[0030] The bonded phase 13 contains an aluminum compound. The aluminum compound includes AlN (aluminum nitride) and Al2O3 (aluminum oxide). The aluminum compound content in the bonded phase 13 may be 5% by mass or more relative to the mass of the bonded phase 13.

[0031] The bonded phase 13 may further contain a titanium compound. The titanium compound includes TiN (titanium nitride) and TiB2 (titanium diboride). The titanium compound may be 70% by mass or more relative to the mass of the bonded phase 13. The bonded phase 13 may contain a titanium compound as its main component. Here, the main component of the bonded phase 13 means 50% by mass or more relative to the mass of the bonded phase 13.

[0032] In the bonded phase 13, AlN, Al2O3, TiN, and TiB2 exist as crystallites constituting the polycrystal. Crystallites are the parts of the polycrystal that can be considered as single crystals. As shown in Figure 4, the bonded phase 13 contains crystallites 13a of AlN, 13b of Al2O3, 13c of TiN, and 13d of TiB2.

[0033] The cBN contained in the hard phase 12 and the AlN, Al2O3, TiN, and TiB2 contained in the bonding phase 13 can be confirmed, for example, by obtaining the X-ray diffraction pattern of the cBN sintered body 11 contained in the substrate 10. The X-ray diffraction pattern of the cBN sintered body 11 contained in the substrate 10 can be obtained, for example, by using an X-ray diffractometer (XRD). An example of an X-ray diffractometer is the "D8 DISCOVER Plus IμS" (manufactured by Bruker Japan).

[0034] Figure 5 is a schematic diagram illustrating the X-ray diffraction pattern of a sintered body according to an embodiment. In Figure 5, the horizontal axis and vertical axis represent the X-ray diffraction angle 2θ(°) and the intensity of the diffracted X-rays (in arbitrary units), respectively. Here, θ(°) is the Bragg angle.

[0035] As shown in Figure 5, the X-ray diffraction pattern of the cBN sintered body 11 includes diffraction peaks such as P_cBN(111) corresponding to the (111) plane of the cBN crystal lattice, P_AlN(100) corresponding to the (100) plane of the AlN crystal lattice, P_Al2O3(104) corresponding to the (104) plane of the Al2O3 crystal lattice, P_TiN(200) corresponding to the (200) plane of the TiN crystal lattice, and P_TiB2(200) corresponding to the (200) plane of the TiB2 crystal lattice. The range of the diffraction angle 2θ in the X-ray diffraction pattern of the cBN sintered body 11 may be, for example, in the range of 30° to 50° when using characteristic X-rays of CuKα with a wavelength of 0.15418 nm.

[0036] As shown in Figure 5, the intensity I_AlN(100) of the diffraction peak P_AlN(100) corresponding to the (100) plane of the AlN crystal lattice in the X-ray diffraction pattern and the intensity I_Al2O3(104) of the diffraction peak P_Al2O3(104) corresponding to the (104) plane of the Al2O3 crystal lattice in the X-ray diffraction pattern are, I_AlN(100)>I_Al2O3(104) ···(1) It satisfies the relationship.

[0037] I_AlN(100) may be the maximum intensity (in arbitrary units) of the diffraction peak P_AlN(100). Similarly, I_Al2O3(104) may be the maximum intensity (in arbitrary units) of the diffraction peak P_Al2O3(104).

[0038] If I_AlN(100) and I_Al2O3(104) satisfy relationship (1), it means that the number of AlN crystallites 13a (see Figure 4) contained in the bonded phase 13 is greater than the number of Al2O3 crystallites 13b (see Figure 4) contained in the bonded phase 13.

[0039] If I_AlN(100) and I_Al2O3(104) satisfy relationship (1), then the intensities of the diffraction peak P_cBN(111) corresponding to the (111) plane of the cBN crystal lattice in the X-ray diffraction pattern, I_cBN(111), I_AlN(100), and I_Al2O3(104), I_AlN(100) / I_cBN(111)>I_Al2O3(104) / I_cBN(111) ···(2) The following relationship is satisfied. That is, relationship (2) may be used instead of relationship (1).

[0040] I_cBN(111) may also be the maximum value (in arbitrary units) of the intensity of the diffraction peak P_cBN(111).

[0041] In the cBN sintered body 11, the crystallite size of AlN with respect to the (100) plane of the AlN crystal lattice, S_AlN(100), and the crystallite size of Al2O3 with respect to the (104) plane of the Al2O3 crystal lattice, S_Al2O3(104), are S_Al2O3(104)>S_AlN(100) ···(3) It satisfies the relationship.

[0042] S_AlN(100) is the size of AlN crystallite 13a (see Figure 4) in the direction normal to the (100) plane of the AlN crystal lattice. Similarly, S_Al2O3(104) is the size of Al2O3 crystallite 13b (see Figure 4) in the direction normal to the (104) plane of the Al2O3 crystal lattice.

[0043] If S_AlN(100) and S_Al2O3(104) satisfy relationship (3), it means that the size of the crystallite 13b of Al2O3 contained in the bonded phase 13 is larger than the size of the crystallite 13a of AlN contained in the bonded phase 13.

[0044] S_AlN(100) and S_Al2O3(104) can be determined, for example, from the X-ray diffraction pattern of the cBN sintered body 11. S_AlN(100) may be calculated, for example, from the full width at half maximum (FMAX) δ_AlN(100) of the diffraction peak P_AlN(100) corresponding to the (100) plane of the AlN crystal lattice in the X-ray diffraction pattern shown in Figure 5, and Scherrer's formula. Similarly, S_Al2O3(104) may be calculated, for example, from the full width at half maximum (FMAX) δ_Al2O3(104) of the diffraction peak P_Al2O3(104) corresponding to the (104) plane of the Al2O3 crystal lattice in the X-ray diffraction pattern shown in Figure 5, and Scherrer's formula. Alternatively, the crystallite size may be calculated from the FMAX using the Paulie method instead of Scherrer's formula.

[0045] δ_AlN(100) may be the full width at half maximum (°) of the diffraction peak P_AlN(100). Similarly, δ_Al2O3(104) may be the full width at half maximum (°) of the diffraction peak P_Al2O3(104).

[0046] The Scherrer equation described above is expressed as S = Kλ / (δ × π / 180 × cosθ). In Scherrer's equation, S, K, λ, δ, and θ are the crystallite size (nm), Scherrer constant, X-ray wavelength (nm), full width at half maximum (FMAX) of the diffraction peak (°), and Bragg angle (°), respectively.

[0047] S_AlN(100) is, for example, S_AlN(100)=Kλ / (δ_AlN(100)×π / 180×cosθ_AlN(100)) ···(4) It is calculated by the following formula. θ_AlN(100) is the Bragg angle (diffraction angle / 2) corresponding to the diffraction peak P_AlN(100).

[0048] Similarly, S_Al2O3(104) is, for example, S_Al2O3(104)=Kλ / (δ_Al2O3(104)×π / 180×cosθ_Al2O3(104)) ···(5) It is calculated by the following formula. θ_Al2O3(104) is the Bragg angle (diffraction angle / 2) corresponding to the diffraction peak P_Al2O3(104).

[0049] Applying equations (4) and (5) to relationship (3), δ_Al2O3(104)×cosθ_Al2O3(104)<δ_AlN(100)×cosθ_AlN(100) ···(6) The following relationship can be obtained. In other words, relationship (6) may be used instead of relationship (3).

[0050] Furthermore, taking into account that cosθ_Al2O3(104) and cosθ_Al2O3(100) are approximately equal, the relationship in (6) δ_Al2O3(104)<δ_AlN(100) ···(7) This can be approximated by the following relationship. In this case, relationship (7) may be used instead of relationship (3).

[0051] As described above, when I_AlN(100) and I_Al2O3(104) satisfy relationship (1) and S_AlN(100) and S_Al2O3(104) satisfy relationship (3), then the number of AlN crystallites 13a is greater than the number of Al2O3 crystallites 13b, and the size of the Al2O3 crystallites 13b is greater than the size of the AlN crystallites 13a.

[0052] Here, the Vickers hardness of the Al2O3 crystal is higher than that of the AlN crystal. That is, the size of the Al2O3 crystallites 13b, which have a higher Vickers hardness, is larger than the size of the AlN crystallites 13a, which have a lower Vickers hardness. This makes it possible to improve the hardness of the binder phase 13. Accordingly, it becomes possible to improve the hardness of the cBN sintered body 11. For example, it becomes possible to improve the wear resistance of the cBN sintered body 11.

[0053] Furthermore, the thermal conductivity of AlN crystals is higher than that of Al2O3 crystals. That is, the number of AlN crystallites 13a with higher thermal conductivity is greater than the number of Al2O3 crystallites 13b with lower thermal conductivity. In addition, the size of the AlN crystallites 13a with higher thermal conductivity is smaller than the size of the Al2O3 crystallites 13b with lower thermal conductivity. As a result, it becomes possible to more uniformly disperse the AlN crystallites 13a with higher thermal conductivity in the bonding phase 13. Accordingly, it becomes possible to improve the thermal conductivity of the bonding phase 13 and reduce the non-uniformity of thermal conductivity in the bonding phase 13. In addition, it becomes possible to more uniformly disperse the AlN crystallites 13a with lower Vickers hardness. As a result, it becomes possible to reduce the hardness bias of the bonding phase 13. Therefore, it becomes possible to reduce the hardness bias of the cBN sintered body 11 even when the temperature rises.

[0054] As a result, it becomes possible to improve the hardness of the cBN sintered body 11 when the temperature rises. In other words, it becomes possible to improve the durability of the cBN sintered body 11 when the temperature rises.

[0055] Accordingly, it becomes possible to improve the durability of insert 1 when the temperature rises. Similarly, it becomes possible to improve the durability of the cutting tool when the temperature rises. For example, it becomes possible to provide a cutting tool that has high durability even when the temperature rises during cutting. In this case, it becomes possible to perform cutting well even when the cutting load increases. By using such a cutting tool, it becomes possible to improve the efficiency of cutting.

[0056] As shown in Figure 5, the intensity I_TiN(200) of the diffraction peak P_TiN(200) corresponding to the (200) plane of the TiN crystal lattice in the X-ray diffraction pattern, the intensity I_TiB2(200) of the diffraction peak P_TiB2(200) corresponding to the (200) plane of the TiB2 crystal lattice in the X-ray diffraction pattern, and I_AlN(100) are, I_AlN(100) <I_TiB2(200)<I_TiN(200) ···(8) The relationship may be satisfied.

[0057] I_TiN(200) may be the maximum intensity (in arbitrary units) of the diffraction peak P_TiN(200). Similarly, I_TiB2(200) may be the maximum intensity (in arbitrary units) of the diffraction peak P_TiB2(200).

[0058] If I_TiN(200), I_TiB2(200), and I_AlN(100) satisfy relationship (8), it means that the number of TiB2 crystallites 13d (see Figure 4) contained in the bonded phase 13 is greater than the number of AlN crystallites 13a contained in the bonded phase 13, and the number of TiN crystallites 13c (see Figure 4) contained in the bonded phase 13 is greater than the number of TiB2 crystallites 13d contained in the bonded phase 13.

[0059] If I_TiN(200), I_TiB2(200), and I_AlN(100) satisfy relationship (8), then I_TiN(200), I_TiB2(200), and I_AlN(100) can be normalized by I_cBN(111) without any problems. I_AlN(100) / I_cBN(111) <I_TiB2(200) / I_cBN(111)<I_TiN(200) / I_cBN(111) ···(9) The following relationship is satisfied. That is, relationship (9) may be used instead of relationship (8).

[0060] In the cBN sintered body 11, the crystallite size of TiN with respect to the (200) plane of the TiN crystal lattice is S_TiN(200), the crystallite size of TiB2 with respect to the (200) plane of the TiB2 crystal lattice is S_TiB2(200), and S_AlN(100) is: S_TiN(200)>S_TiB2(200)>S_AlN(100) ···(10) It satisfies the relationship.

[0061] S_TiN(200) is the size of TiN crystallite 13c (see Figure 4) in the direction normal to the (200) plane of the TiN crystal lattice. Similarly, S_TiB2(200) is the size of TiB2 crystallite 13d (see Figure 4) in the direction normal to the (200) plane of the TiB2 crystal lattice.

[0062] If S_TiN(200), S_TiB2(200), and S_AlN(100) satisfy relationship (10), it means that the size of the crystallite 13d of TiB2 contained in the bonded phase 13 is larger than the size of the crystallite 13a of AlN contained in the bonded phase 13, and the size of the crystallite 13c of TiN contained in the bonded phase 13 is larger than the size of the crystallite 13d of TiB2 contained in the bonded phase 13.

[0063] S_TiN(200) and S_TiB2(200) can be determined, for example, from the X-ray diffraction pattern of the cBN sintered body 11. S_TiN(200) is calculated, for example, from the full width at half maximum (FMAX) δ_TiN(200) of the diffraction peak P_TiN(200) corresponding to the (200) plane of the TiN crystal lattice in the X-ray diffraction pattern shown in Figure 5, and from Scherrer's formula. Similarly, S_TiB2(200) is calculated, for example, from the full width at half maximum (FMAX) δ_TiB2(200) of the diffraction peak P_TiB2(200) corresponding to the (200) plane of the TiB2 crystal lattice in the X-ray diffraction pattern shown in Figure 5, and from Scherrer's formula.

[0064] δ_TiN(200) may be the full width at half maximum (°) of the diffraction peak P_TiN(200). Similarly, δ_TiB2(200) may be the full width at half maximum (°) of the diffraction peak P_TiB2(200).

[0065] S_TiN(200) is, for example, S_TiN(200)=Kλ / (δ_TiN(200)×π / 180×cosθ_TiN(200)) ···(11) It is calculated by the following formula. θ_TiN(200) is the Bragg angle (diffraction angle / 2) corresponding to the diffraction peak P_TiN(200).

[0066] Similarly, S_TiB2(200) is, for example, S_TiB2(200)=Kλ / (δ_TiB2(200)×π / 180×cosθ_TiB2(200)) ···(12) It is calculated by the following formula. θ_TiB2(200) is the Bragg angle (diffraction angle / 2) corresponding to the diffraction peak P_TiB2(200).

[0067] Applying equations (4), (11), and (12) to relationship (10), δ_TiN(200)×cosθ_TiN(200)<δ_TiB2(200)×cosθ_TiB2(200)<δ_AlN(100)×cosθ_AlN(100) ···(13) The following relationship can be obtained. That is, instead of relationship (10), relationship (13) may be used.

[0068] Furthermore, taking into account that cosθ_TiN(200), cosθ_TiB2(200), and cosθ_AlN(100) are approximately equal, the relationship in (13) is δ_TiN(200)<δ_TiB2(200)<δ_AlN(100) ···(14) This can be approximated by the relationship (10). In this case, relationship (14) may be used instead of relationship (10).

[0069] As described above, if I_TiN(200), I_TiB2(200), and I_AlN(100) satisfy relationship (8) and S_TiN(200), S_TiB2(200), and S_AlN(100) satisfy relationship (10), then the number of crystallites 13d of TiB2 is greater than the number of crystallites 13a of AlN, the number of crystallites 13c of TiN is greater than the number of crystallites 13d of TiB2, the size of the crystallites 13d of TiB2 is greater than the size of the crystallites 13a of AlN, and the size of the crystallites 13c of TiN is greater than the size of the crystallites 13d of TiB2.

[0070] In this case, it becomes possible to improve thermal conductivity. TiN has lower thermal conductivity compared to TiB2. If the size of the TiN crystallite 13c is larger than the size of the TiB2 crystallite 13d, the decrease in thermal conductivity in the TiN crystallite 13c can be mitigated. Therefore, it is possible to reduce the decrease in thermal conductivity while still containing the TiN crystallite 13c. As a result, the risk of thermal cracking in the substrate 10 can be reduced.

[0071] In the cBN sintered body 11, S_Al2O3(104) and S_TiN(200) are, S_Al2O3(104)>S_TiN(200) ···(15) The relationship may be satisfied.

[0072] If S_Al2O3(104) and S_TiN(200) satisfy relationship (15), it means that the size of the crystallite 13b of Al2O3 contained in the bonded phase 13 is larger than the size of the crystallite 13c of TiN contained in the bonded phase 13.

[0073] Applying equations (5) and (11) to relationship (15), δ_Al2O3(104)×cosθ_Al2O3(104)<δ_TiN(200)×osθ_TiN(200) ...(16) The following relationship can be obtained. That is, relationship (16) may be used instead of relationship (15).

[0074] Furthermore, taking into account that cosθ_Al2O3(104) and cosθ_TiN(200) are approximately equal, the relationship in (16) δ_Al2O3(104)<δ_TiN(200) ···(17) This can be approximated by the relationship (15). In this case, relationship (17) may be used instead of relationship (15).

[0075] As described above, when S_Al2O3(104) and S_TiN(200) satisfy relationship (15), the size of the crystallite 13b of Al2O3 is larger than the size of the crystallite 13c of TiN.

[0076] In this case, it becomes possible to improve the wear resistance of the substrate 10. Al2O3 has higher hardness compared to TiN. When the size of the crystallites 13b of such hard Al2O3 is relatively large, the progression of wear in the Al2O3 crystallites 13b is easily suppressed. Therefore, as described above, it becomes possible to improve the wear resistance of the substrate 10.

[0077] In the cBN sintered body 11, both S_Al2O3(104) and S_TiN(200) may have a wavelength of 60 nm or more.

[0078] As mentioned above, if both S_Al2O3(104) and S_TiN(200) are 60 nm or larger, then the average size of the 13b crystallite of Al2O3 and the average size of the 13c crystallite of TiN are both approximately 60 nm or larger.

[0079] The above-mentioned I_cBN(111), I_AlN(100), δ_AlN(100), θ_AlN(100), S_AlN(100), I_Al2O3(104), δ_Al2O3(104), θ_Al2O3(104), S_Al2O3(104), I_TiN(200), δ_TiN(200), θ_TiN(200), S_TiN(200), I_TiB2(200), δ_TiB2(200), θ_TiB2(200), and S_TiB2(200) can be obtained using X-ray diffraction software. Examples of X-ray diffraction software include Bruker's "TOPAS".

[0080] <Cutting tools> Next, the configuration of the cutting tool equipped with the insert 1 described above will be explained with reference to Figure 6. Figure 6 is a front view showing an example of a cutting tool according to the embodiment. The cutting tool is used for cutting a workpiece. This produces a cut workpiece. Examples of cutting processes include turning and milling.

[0081] As shown in Figure 6, the cutting tool 100 according to this embodiment comprises an insert 1 and a holder 70 for fixing the insert 1.

[0082] The holder 70 is a rod-shaped member extending from the tip (upper end in Figure 6) to the rear end (lower end in Figure 6). The holder 70 is made of, for example, steel or cast iron. Among these materials, steel with high toughness may be used.

[0083] The holder 70 has a pocket 73 located at the end on the tip side. The pocket 73 is the part into which the insert 1 is fitted, and has a seating surface that intersects with the rotational direction of the workpiece, and a restraining side surface that is inclined with respect to the seating surface. The seating surface is provided with a screw hole into which a screw 75, which will be described later, is screwed.

[0084] Insert 1 is located within the pocket 73 of the holder 70 and is attached to the holder 70 by a screw 75. Specifically, the screw 75 is inserted into the through hole 5 of the insert 1, and the tip of the screw 75 is inserted into the screw hole formed in the seating surface of the pocket 73, thereby screwing the screw portions together. In this way, the insert 1 is attached to the holder 70 such that the cutting edge 8 protrudes outward from the holder 70.

[0085] In this embodiment, a cutting tool 100 used for so-called turning operations is illustrated. Examples of turning operations include internal diameter machining, external diameter machining, grooving, and parting. The cutting tool is not limited to those used for turning operations. For example, an insert 1 may be used as a cutting tool for milling operations. Examples of cutting tools used for milling operations include milling cutters such as flat milling cutters, face milling cutters, side milling cutters, or groove milling cutters, and end mills such as single-flute end mills, multi-flute end mills, tapered end mills, or ball end mills.

[0086] In this embodiment, an example is shown where the top and bottom surfaces of the cutting tool 100 are parallelograms. The top and bottom surfaces of the cutting tool 100 may also be rhombic, square, etc. The top and bottom surfaces of the cutting tool 100 may also be triangular, pentagonal, hexagonal, etc. The shape of the cutting tool 100 may be positive or negative. The positive type is a type in which the side surface is inclined with respect to a central axis passing through the center of the top surface and the center of the bottom surface of the cutting tool 100, while the negative type is a type in which the side surface is parallel to the above central axis.

[0087] <Method for manufacturing machined parts> Next, a method for manufacturing a machined workpiece according to an embodiment will be described with reference to Figures 7A, 7B, and 7C. Figures 7A, 7B, and 7C are schematic diagrams showing one step of the method for manufacturing a machined workpiece according to an embodiment.

[0088] The machined workpiece 200 is produced by machining the workpiece 201. Figures 7A, 7B, and 7C illustrate turning using a lathe as an example of machining. The method for manufacturing the machined workpiece 200 in this embodiment is as follows: The process of rotating the workpiece 201 (process A), Step B involves bringing the workpiece 201 and the cutting tool 100 into contact, Step C involves moving the cutting tool 100 relatively away from the workpiece 201, It is equipped with.

[0089] More specifically, first, as shown in Figure 7A, the workpiece 201 is rotated around the axis O1, and the cutting tool 100 is brought relatively close to the workpiece 201. Next, as shown in Figure 7B, the cutting edge 8 (see Figure 1) of the insert 1 is brought into contact with the workpiece 201, and the workpiece 201 is cut. Next, as shown in Figure 7C, the cutting tool 100 is moved relatively away from the workpiece 201.

[0090] In Figure 7A, the cutting tool 100 is moved closer to the workpiece 201 by moving it in the Y1 direction while the shaft O1 is fixed and the workpiece 201 is rotating. In Figure 7B, the workpiece 201 is cut by bringing the cutting edge 8 of the insert 1 into contact with the rotating workpiece 201. In Figure 7C, the cutting tool 100 is moved away from the workpiece 201 by moving it in the Y2 direction while the workpiece 201 is rotating.

[0091] In the cutting process of the manufacturing method for a machined workpiece according to this embodiment, the cutting tool 100 is moved in each step to bring the cutting tool 100 into contact with the workpiece 201 or to move the cutting tool 100 away from the workpiece 201. However, the manufacturing method for a machined workpiece is, of course, not limited to this form.

[0092] For example, in step A, the workpiece 201 may be brought close to the cutting tool 100. Similarly, in step C, the workpiece 201 may be moved away from the cutting tool 100. When continuing the cutting process, the state where the workpiece 201 is rotated may be maintained, and the step of bringing the cutting edge 8 of the cutting tool 100 into contact with different positions of the workpiece 201 may be repeated.

[0093] When performing milling instead of turning, the cutting tool may be rotated around the rotation axis in step A. Further, in step B, the workpiece 201 may be cut by bringing the rotating cutting edge 8 of the insert 1 into contact with the workpiece 201. Furthermore, in step C, the cutting tool may be moved away from the workpiece 201 by moving the cutting tool. The milling may be performed using a milling machine.

[0094] Representative examples of the material of the workpiece 201 include carbon steel, alloy steel, stainless steel, cast iron, non-ferrous metals, and the like.

[0095] <Method for producing cBN-based sintered body and insert> Next, an example of the method for producing the cBN-based sintered body and the insert according to the embodiment will be described. The method for producing the cBN-based sintered body and the insert is not limited to the method shown below.

[0096] First, a TiN raw material powder of 72 vol% or more and 82 vol% or less, an Al raw material powder of 13 vol% or more and 23 vol% or less, and an Al₂O₃ raw material powder of 1 vol% or more and 11 vol% or less are prepared. Next, an organic solvent is added to the prepared mixture of each raw material powder. As the organic solvent, alcohols such as acetone and isopropyl alcohol (IPA) can be used. Thereafter, the mixture of each raw material powder to which the organic solvent is added is pulverized and mixed in a ball mill for 20 hours or more and 24 hours or less. After pulverization and mixing, the organic solvent is evaporated to obtain a first mixed powder.

[0097] Next, cBN powder with an average particle size of 2.5 μm to 4.5 μm and cBN powder with an average particle size of 0.5 μm to 1.5 μm are mixed in a volume ratio of 8 to 9:1 to 2. Furthermore, an organic solvent is added to each cBN powder mixture. Alcohols such as acetone and IPA can be used as the organic solvent. After that, each cBN powder mixture with the added organic solvent is pulverized and mixed in a ball mill for 20 to 24 hours. After pulverization and mixing, the organic solvent is evaporated to obtain the second mixed powder.

[0098] Next, the obtained first mixed powder and second mixed powder are blended in a volume ratio of 68 to 78:22 to 32. An organic solvent and an organic binder are added to the mixture of the first and second mixed powders. Alcohols such as acetone and IPA can be used as the organic solvent. Paraffin, acrylic resins, etc. can be used as the organic binder. Then, the mixture of the first and second mixed powders with the added organic solvent and organic binder is pulverized and mixed in a ball mill for 20 to 24 hours. After pulverization and mixing, the organic solvent is evaporated to obtain the third mixed powder. A dispersant may be added as needed in the ball milling process.

[0099] Next, a molded body is obtained by molding the resulting third mixed powder into a predetermined shape. Known methods such as uniaxial press and cold isostatic press (CIP) can be used for molding. The obtained molded body is heated to a predetermined temperature in the range of 300°C to 600°C to evaporate and remove the organic binder.

[0100] Next, the molded body from which the organic binder has been removed is placed in an ultra-high pressure heating device and heated at a temperature of 1200°C to 1500°C for 15 minutes to 30 minutes under a pressure of 4 GPa to 6 GPa. This yields the cBN sintered body 11 according to the embodiment.

[0101] Next, the obtained cBN sintered body 11 is attached as a base body 10 to the seating surface 4 of the main body 2 of the insert 1 made of cemented carbide via a bonding material 40 to produce the insert 1 according to the embodiment. A coating film 20 may be formed on the surface of the base body 10 and the main body 2 by physical vapor deposition (PVD). [Examples]

[0102] The embodiments of this disclosure will be described below in detail. This disclosure is not limited to the embodiments shown below.

[0103] (Examples) First, 80 vol% TiN raw material powder, 15 vol% Al raw material powder, and 5 vol% Al2O3 raw material powder were prepared. Next, an organic solvent was added to the mixture of each prepared raw material powder. Then, the mixture of each raw material powder with the added organic solvent was pulverized and mixed in a ball mill. After pulverization and mixing, the organic solvent was evaporated to obtain the first mixed powder.

[0104] Next, cBN powder with an average particle size of 2-10 μm and cBN powder with an average particle size of 0.05-0.8 μm were prepared. The preparation may be adjusted so that the 2-10 μm cBN powder accounts for approximately 50-95% by volume. Furthermore, an organic solvent was added to each cBN powder preparation. Subsequently, the preparations of each cBN powder with the added organic solvent were pulverized and mixed using a ball mill. After pulverization and mixing, the organic solvent was evaporated to obtain a second mixed powder.

[0105] Next, the obtained first mixed powder and second mixed powder were mixed. An organic solvent, an organic binder, and a dispersant were added to the mixture of the first and second mixed powders. Then, the mixture of the first and second mixed powders with the added organic solvent, organic binder, and dispersant was pulverized and mixed in a ball mill for 10 hours. After pulverization and mixing, the organic solvent was evaporated to obtain the third mixed powder.

[0106] Next, a molded body was obtained from the resulting third mixed powder using a well-known method such as press molding. The resulting molded body was heated to evaporate and remove the organic binder.

[0107] Next, the molded body from which the organic binder had been removed was placed in an ultra-high pressure heating device and heated at a temperature of 1200 to 1600°C under a pressure of 4 to 6 GPa. This yielded a cBN sintered body according to the example.

[0108] Next, the X-ray diffraction pattern of the cBN sintered body according to the example was obtained using the X-ray diffractometer "D8 DISCOVER Plus IμS" (manufactured by Bruker Japan). Figure 8 shows the X-ray diffraction pattern of the cBN sintered body according to the example. In Figure 8, the horizontal axis and vertical axis represent the X-ray diffraction angle 2θ (°) and the intensity of the diffracted X-rays (in arbitrary units), respectively.

[0109] As shown in Figure 8, the X-ray diffraction pattern of the cBN sintered body according to the example included diffraction peaks corresponding to the (111) plane of the cBN crystal lattice, diffraction peaks corresponding to the (100) plane of the AlN crystal lattice, diffraction peaks corresponding to the (104) plane of the Al2O3 crystal lattice, diffraction peaks corresponding to the (200) plane of the TiN crystal lattice, and diffraction peaks corresponding to the (200) plane of the TiB2 crystal lattice.

[0110] Next, using the X-ray diffraction software "TOPAS" (manufactured by Bruker), the intensity I (in arbitrary units) and crystallite size S (nm) associated with the above diffraction peaks were calculated for the X-ray diffraction pattern of the cBN sintered body according to the example, as shown below. I_cBN(111)=1065.8842 I_AlN(100) = 116.1263 I_Al2O3(104) = 84.2432 I_TiN(200) = 1687.9974 I_TiB2(200) = 460.4095 S_AlN(100) = 36.2 nm S_Al2O3(10⁴) = 68 nm S_TiN(200) = 66.8 nm S_TiB2(200) = 58nm

[0111] Thus, the X-ray diffraction pattern of the cBN sintered body according to the example is as follows: I_AlN(100)>I_Al2O3(104) I_AlN(100) / I_cBN(111)>I_Al2O3(104) / I_cBN(111) S_Al2O3(104)>S_AlN(100) I_AlN(100) <I_TiB2(200)<I_TiN(200) I_AlN(100) / I_cBN(111) <I_TiB2(200) / I_cBN(111)<I_TiN(200) / I_cBN(111) S_TiN(200)>S_TiB2(200)>S_AlN(100) S_Al2O3(104)>S_TiN(200) S_Al2O3(10⁴)≧60nm S_TiN(200)≧60nm It was confirmed that all of the following relationships were satisfied.

[0112] (Comparative example) The X-ray diffraction pattern of commercially available cBN sintered body A, used as a comparative example, was obtained using the X-ray diffractometer "D8 DISCOVER Plus IμS" (manufactured by Bruker Japan). Figure 9 shows the X-ray diffraction pattern of the cBN sintered body of the comparative example. In Figure 9, the horizontal axis and vertical axis represent the X-ray diffraction angle 2θ (°) and the intensity of the diffracted X-rays (in arbitrary units), respectively.

[0113] As shown in Figure 9, the X-ray diffraction pattern of the comparative example cBN sintered body included diffraction peaks corresponding to the (111) plane of the cBN crystal lattice, diffraction peaks corresponding to the (100) plane of the AlN crystal lattice, and diffraction peaks corresponding to the (104) plane of the Al2O3 crystal lattice.

[0114] Next, using the X-ray diffraction software "TOPAS" (manufactured by Bruker), the intensity I (in arbitrary units) and crystallite size S (nm) associated with the above diffraction peaks were calculated for the cBN sintered body of the comparative example, as shown below. I_cBN(111)=899.4935 I_AlN(100) = 54.5619 I_Al2O3(104) = 74.6342 I_TiN(200) = 1238.901 I_TiB2(200) = 168.5844 S_AlN(100) = 44 nm S_Al2O3(10⁴) = 51.0 nm S_TiN(200) = 57.8 nm S_TiB2(200) = 41.8 nm

[0115] Thus, the X-ray diffraction pattern of the cBN sintered body in the comparative example is as follows: S_Al2O3(104)>S_AlN(100) The relationship is satisfied, I_AlN(100)>I_Al2O3(104) I_AlN(100) / I_cBN(111)>I_Al2O3(104) / I_cBN(111) It was confirmed that none of the following relationships were satisfied.

[0116] Next, a cutting tool according to the example, which includes a substrate made of a cBN sintered body according to the example, and a cutting tool according to the comparative example, which includes a substrate made of a cBN sintered body according to the comparative example, were prepared.

[0117] Next, a wear resistance evaluation test was performed as a cutting test for each of the cutting tools according to the example and the comparative example. The cutting conditions in the wear resistance evaluation test are shown below.

[0118] • Cutting conditions for wear resistance evaluation test Cutting method: Turning and external diameter machining Workpiece material: SCM415 (carburized and hardened steel) Cutting speed: 150m / min Feed rate: 0.1 mm / revolution Cutting depth: 0.2mm Cutting method: Wet Tool used: CNGA120408S01225 Evaluation Method: Using images showing the cutting edge condition of the cutting tool after a predetermined cutting time, the length of nose wear (nose wear amount) (mm) in the thickness direction of the substrate contained in the cutting tool was measured. The predetermined cutting times were 0.9 minutes, 2.6 minutes, 5.2 minutes, 10.5 minutes, 15.7 minutes, 20.9 minutes, 26.2 minutes, 31.4 minutes, 36.6 minutes, 41.9 minutes, and 47.1 minutes.

[0119] Figure 10 shows the results of wear resistance evaluation tests for cutting tools according to the embodiment and cutting tools according to the comparative example. In Figure 10, the horizontal axis and vertical axis represent cutting time (minutes) and nose wear amount (mm), respectively.

[0120] As shown in Figure 10, the nose wear of the cutting tool in the embodiment for cutting times of 0.9 minutes, 2.6 minutes, 5.2 minutes, 10.5 minutes, 15.7 minutes, 20.9 minutes, 26.2 minutes, 31.4 minutes, 36.6 minutes, 41.9 minutes, and 47.1 minutes was 0.021 mm, 0.024 mm, 0.028 mm, 0.035 mm, 0.041 mm, 0.048 mm, 0.062 mm, 0.066 mm, 0.080 mm, 0.090 mm, and 0.144 mm, respectively.

[0121] As shown in Figure 10, the nose wear of the cutting tool for the comparative example at cutting times of 0.9 minutes, 2.6 minutes, 5.2 minutes, 10.5 minutes, 15.7 minutes, 20.9 minutes, 26.2 minutes, 31.4 minutes, 36.6 minutes, and 41.9 minutes was 0.020 mm, 0.026 mm, 0.034 mm, 0.038 mm, 0.051 mm, 0.063 mm, 0.073 mm, 0.087 mm, 0.096 mm, and 0.142 mm, respectively.

[0122] Thus, it was confirmed that, during the common cutting time from 2.6 minutes onward, the amount of nose wear of the cutting tool in the embodiment was less than that of the cutting tool in the comparative example. Generally, the temperature of the cutting tool rises as the cutting time increases. Therefore, even when the temperature rises, the amount of nose wear of the cutting tool in the embodiment is considered to be less than that of the cutting tool in the comparative example. In other words, the durability of the cutting tool in the embodiment when the temperature rises is considered to be higher than that of the cutting tool in the comparative example when the temperature rises.

[0123] Next, a stability evaluation test was performed as a cutting test for each of the cutting tools according to the example and the comparative example. The cutting conditions in the stability evaluation test are shown below.

[0124] • Cutting conditions for stability evaluation test Cutting method: Turning and face machining Workpiece material: SCM415 (carburized and hardened steel) 8 holes (φ10mm) Cutting speed: 150m / min Feed speed: 0.2 mm / revolution Cutting depth: 0.2mm Tool used: CNGA120408S01225 Evaluation method: The number of impacts (times) when the cutting edge of the cutting tool was chipped was measured.

[0125] The number of impacts at which the cutting edge of the cutting tool in the example broke was 14,800. The number of impacts at which the cutting edge of the cutting tool in the comparative example broke was 11,800.

[0126] Thus, it was confirmed that the number of impacts at which the cutting edge of the cutting tool in the embodiment broke was greater than the number of impacts at which the cutting edge of the cutting tool in the comparative example broke. In other words, it was confirmed that, for a common number of impacts, the frequency of cutting edge breakage in the cutting tool in the embodiment was lower than the frequency of cutting edge breakage in the cutting tool in the comparative example. Generally, the temperature of the cutting tool rises as the number of impacts increases. Therefore, even when the temperature rises, the frequency of cutting edge breakage in the cutting tool in the embodiment is considered to be lower than the frequency of cutting edge breakage in the cutting tool in the comparative example. That is, the durability of the cutting tool in the embodiment when the temperature rises is considered to be higher than the durability of the cutting tool in the comparative example when the temperature rises.

[0127] As described above, we were able to confirm that the durability of cBN sintered bodies can be improved when I_AlN(100) and I_Al2O3(104) satisfy the relationship I_AlN(100)>I_Al2O3(104), and S_AlN(100) and S_Al2O3(104) satisfy the relationship S_Al2O3(104)>S_AlN(100).

[0128] This technology can take the following configuration. (1) A hard phase containing cubic boron nitride, It contains AlN and Al2O3, and a binding phase that binds the hard phase Includes, The intensity of the diffraction peak corresponding to the (100) plane of the AlN crystal lattice in the X-ray diffraction pattern, I_AlN(100), and the intensity of the diffraction peak corresponding to the (104) plane of the Al2O3 crystal lattice in the same X-ray diffraction pattern, I_Al2O3(104), I_AlN(100)>I_Al2O3(104) Satisfying the relationship, The crystallite size S_AlN(100) of AlN with respect to the (100) plane of the AlN crystal lattice and the crystallite size S_Al2O3(104) of Al2O3 with respect to the (104) plane of the Al2O3 crystal lattice are: S_Al2O3(104)>S_AlN(100) Satisfying the relationship, Sintered body. (2) The bonded phase further contains TiN and TiB2, The intensity of the diffraction peak corresponding to the (200) plane of the TiN crystal lattice in the aforementioned X-ray diffraction pattern, I_TiN(200), the intensity of the diffraction peak corresponding to the (200) plane of the TiB2 crystal lattice in the aforementioned X-ray diffraction pattern, I_TiB2(200), and I_AlN(100) are, I_AlN(100) <I_TiB2(200)<I_TiN(200) Satisfying the relationship, The crystallite sizes of TiN with respect to the (200) plane of the TiN crystal lattice are S_TiN(200), TiB2 with respect to the (200) plane of the TiB2 crystal lattice are S_TiB2(200), and S_AlN(100). S_TiN(200)>S_TiB2(200)>S_AlN(100) Satisfying the relationship, The sintered body described in (1) above. (3) S_Al2O3(104) and S_TiN(200) are, S_Al2O3(104)>S_TiN(200) Satisfying the relationship, The sintered body described in (2) above. (4) Both S_Al2O3(104) and S_TiN(200) have a wavelength of 60 nm or more. The sintered body described in (2) or (3) above. (5) The insert body and A substrate located on the insert body and comprising a sintered body as described in any one of (1) to (4), An insert equipped with... (6) A holder having a pocket that extends from the tip towards the rear end and is located on the side of the tip, The insert described in (5) located in the aforementioned pocket and A cutting tool equipped with the following features. (7) A step of rotating the workpiece or the cutting tool described in (6) above, A step of bringing the workpiece and the cutting tool into contact, A step of moving the cutting tool relatively away from the workpiece. Equipped with, A method for manufacturing machined parts.

[0129] Further effects and / or modifications can be readily derived by those skilled in the art. Therefore, broader aspects of the present invention are not limited to the specific details and representative embodiments expressed and described above. Accordingly, various modifications are possible without departing from the spirit or scope of the overall concept of the invention as defined by the appended claims and their equivalents. [Explanation of Symbols]

[0130] 1 Insert 2 Main body 4 Seat 5 Through hole 6 Front page 7 Side 2 8 cutting edges 10 Base 11 cBN sintered body 12 Hard phase 12a cBN particles 13 Bonded phase 13a AlN crystallite 13b Crystallite of Al2O3 Crystallites of 13c TiN 13d TiB2 crystallite 20 Coating membrane 30 circuit boards 40 Bonding material 70 Holder 73 pockets 75 screws 100 cutting tools 200 Cutting workpiece 201 Work material O1 axis

Claims

1. A hard phase containing cubic boron nitride, AlN and Al 2 O 3 It contains and a binding phase that binds the hard phase Includes, The intensity of the diffraction peak corresponding to the (100) plane of the AlN crystal lattice in the X-ray diffraction pattern I_AlN(100) and the Al in the X-ray diffraction pattern 2 O 3 The intensity of the diffraction peak corresponding to the (104) plane of the crystal lattice I_Al 2 O 3 (104) is, I_AlN(100)>I_Al 2 O 3 (104) Satisfying the relationship, AlN crystallite size S_AlN(100) for the (100) plane of the AlN crystal lattice and Al 2 O 3 for the (104) plane of the crystal lattice of 2 O 3 crystallite size S_Al 2 O 3 (104) are S_Al 2 O 3 (104)>S_AlN(100) Satisfying the relationship, Sintered body.

2. The aforementioned bonding phase consists of TiN and TiB 2 It further contains, The intensity of the diffraction peak corresponding to the (200) plane of the TiN crystal lattice in the aforementioned X-ray diffraction pattern is I_TiN(200), and the intensity of the diffraction peak corresponding to the (200) plane of the TiN crystal lattice in the aforementioned X-ray diffraction pattern is TiB 2 The intensity of the diffraction peak corresponding to the (200) plane of the crystal lattice I_TiB 2 (200), and I_AlN(100) are, I_AlN(100)<I_TiB 2 (200)<I_TiN(200) Satisfying the relationship, Crystallite size of TiN for the (200) plane of the TiN crystal lattice S_TiN(200), TiB 2 TiB for the (200) plane of the crystal lattice 2 Crystallite size S_TiB 2 (200), and S_AlN(100) are, S_TiN(200)>S_TiB 2 (200)>S_AlN(100) Satisfying the relationship, The sintered body according to claim 1.

3. S_Al 2 O 3 (104) and S_TiN(200) are, S_Al 2 O 3 (104)>__TiN (200) Satisfying the relationship, The sintered body according to claim 2.

4. S_Al 2 O 3 Both (104) and S_TiN(200) have a wavelength of 60 nm or more. The sintered body according to claim 2 or 3.

5. The insert body and A substrate located on the insert body and comprising a sintered body according to any one of claims 1 to 4, An insert equipped with...

6. A holder having a pocket that extends from the tip towards the rear end and is located on the side of the tip, The insert according to claim 5 located in the aforementioned pocket A cutting tool equipped with the following features.

7. A step of rotating the workpiece or the cutting tool described in claim 6, A step of bringing the workpiece and the cutting tool into contact, A step of moving the cutting tool relatively away from the workpiece. Equipped with, A method for manufacturing machined parts.

Citation Information

Patent Citations

  • Insert and cutting tool

    WO2022004530A1